Acknowledging the enslaved Other (Altre Modernità, 2016)
Acknowledging the enslaved Other (Pietro Deandrea, New Slaveries in Contemporary British Literature and Visual Arts: The ghost and the camp, Manchester, Manchester University Press, 2015, 236 pp. ISBN 978-0-7190-9643-3)by Lidia De Michelis